Advances in electron transfer chemistry. - Mariano, Patrick S. (Advances in electron transfer chemistry, 1993)
Advances in Electron Transfer Chemistry, Volume 3 presents studies that discuss findings in the various aspects of electron chemistry. The book is comprised of four chapters; each chapter reviews a work that tackles an issue in electron transfer chemistry. Chapter 1 discusses the photoinduced electron transfer in flexible biaryl donor-acceptor molecules. Chapter 2 tackles light-induced electron transfer in inorganic systems in homogeneous and heterogeneous phases. The book also covers internal geometry relaxation effects on electron transfer rates of amino-centered systems. The sequential elec.